Structure and superconductivity of (Li1−xFex)OHFeSe single crystals grown using AxFe2−ySe2 (A = K, Rb, and Cs) as precursors. (10th December 2015) - Yu, G; Zhang, G Y; Ryu, G H; Lin, C T
Abstract: We present results on the hydrothermal growth of ( )OHFeSe single crystals using floating-zone-grown ( A = K, Rb, and Cs) as precursors. The growth proceeds by the hydrothermal ion exchange of Li/Fe–O–H for K, Rb, and Cs, resulting in a stacking layer of ( )OH sandwiched between the FeSe layers. Optimal growth parameters are achieved using high quality A 0.80 Fe1.81 Se2 single crystals added to the mixtures of LiOH, H2 O, Fe and C(NH2 )2 Se in an autoclave and subsequently heated to 120 °C for 2 d, to obtain highest quality single crystals. The obtained crystals have lateral dimensions up to centimeters, with the final size related to that of the precursor crystal used. All ( )OHFeSe single crystals show a superconducting transition temperature T c > 42 K, regardless of the phase of the precursor such as superconducting K0.80 Fe1.81 Se2 ( T c = 29.31 K) or non-superconducting Rb0.80 Fe1.81 Se2 or poor-superconducting Cs0.80 Fe1.81 Se2 ( T c = 28.67 K). The T c and transition width Δ T vary in the obtained single crystals, due to the inhomogeneity of the ionic exchange. X-ray diffraction analysis demonstrates that the 245 insulating phase is absent in the ion-exchanged single crystals, while it is observed in the precursors. Comparative studies of the structure, magnetization, and superconductivity on the parent A 0.80 Fe1.81 Se2 and the ion-exchanged ( )OHFeSe crystals are discussed. A phase diagram including antiferromagnetic spin density wave and superconducting phases is also proposed.